FAKTOR DOMINAN PENYEBAB KEJADIAN ANEMIA PADA REMAJA - Gani, Kameriah; Rotinsulu, Ria Angelina Jessica; Witari, Ni Nyoman Deni; Mahardika, Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Anemia is a significant global health problem that affects many individuals around the world. Adolescent girls have a higher risk of developing anemia. Based on an initial survey conducted on adolescent girls in several schools in Kendari city, information was obtained indicating the potential incidence of anemia which in the examination was found to be around 25% anemic. The purpose of the study was to determine the dominant factors causing the incidence of anemia in adolescents. The research design used in this study was cross sectional. The research was conducted in the Kendari City area. The research was conducted in November 2023. The study population was all adolescent girls in Kendari City District. The selected sample amounted to 64 people. The sampling technique used Simple Random Sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed that the dominant factor causing the incidence of anemia in adolescent girls was menstrual patterns (p value: 0.037). It is recommended for teenagers to always consume nutritious foods and can consume blood supplement tablets every menstruation.Keywords: Anemia, Menstrual Pattern, Adolescents.